Paham Gereja Katolik tentang Indulgensi - Alexius Poto Obe; Antonius P Sipahutar; Margaretha Niat Hati Zalukhu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This article departs from concern over the lack of understanding of Catholic believers about the usefulness of indulgences given by the Church. The main problem raised is the lack of understanding of the faithful in understanding the Church's teaching on indulgences. The purpose of writing this thesis is for Catholic believers to understand more correctly and appropriately the Church's teaching about indulgences. The method used in this thesis is a literature review. The result of the discussion obtained is that Catholic believers can understand and utilize indulgences, increasingly strive to live holy, and try to be grateful and use these indulgences as well as possible. The conclusion of this writing is that the understanding of indulgences needs to be given by the Church in the form of catechesis so that the people are more aware of the benefits of these indulgences.